Myelin heterogeneity for assessing normal appearing white matter myelin damage in multiple sclerosis. Issue 2 (28th November 2022) - Johnson, Poljanka; Vavasour, Irene M.; Stojkova, Biljana Jonoska; Abel, Shawna; Lee, Lisa Eunyoung; Laule, Cornelia; Tam, Roger; Li, David K. B.; Ackermans, Nathalie; Schabas, Alice J.; Chan, Jillian; Cross, Helen; et al.
Abstract: Background and Purpose: Conventional MRI measures of multiple sclerosis (MS) disease severity, such as lesion volume and brain atrophy, do not provide information about microstructural tissue changes, which may be driving physical and cognitive progression. Myelin damage in normal‐appearing white matter (NAWM) is likely an important contributor to MS disability. Myelin water fraction (MWF) provides quantitative measurements of myelin. Mean MWF reflects average myelin content, while MWF standard deviation (SD) describes variation in myelin within regions. The myelin heterogeneity index (MHI = SD/mean MWF) is a composite metric of myelin content and myelin variability. We investigated how mean MWF, SD, and MHI compare in differentiating MS from controls and their associations with physical and cognitive disability. Methods: Myelin water imaging data were acquired from 91 MS participants and 31 healthy controls (HC). Segmented whole‐brain NAWM and corpus callosum (CC) NAWM, mean MWF, SD, and MHI were compared between groups. Associations of mean MWF, SD, and MHI with Expanded Disability Status Scale and Symbol Digit Modalities Test were assessed. Results: NAWM and CC MHI had the highest area under the curve: .78 (95% confidence interval [CI]: .69, .86) and .84 (95% CI: .76, .91), respectively, distinguishing MS from HC. Conclusions: Mean MWF, SD, and MHI provide complementary information when assessing regional and global NAWM abnormalities in MS and associations with clinical outcome measures. Examining all three metrics (mean MWF, SD, and MHI) enables a more detailed interpretation of results, depending on whether regions of interest include areas that are more heterogeneous, earlier in the demyelination process, or uniformly injured.